Business models and modelling - Baden Fuller, C. 1948-; Mangematin, V. (Emerald, 2015)
In this volume, leading scholars from North America, Europe, and Asia come together to explore new dimensions of the business models topic paying particular attention to the modelling dimension - what this means , how modelling should be approached, how business models are manipulated, how they become iconic, and why they are embedded in heuristics. These ideas are a new departure for the literature that allows more solid theorizing about the role of business models in conceptions of strategy and strategizing. It also allows the demand side perspective (customers and their engagement) to become clearer, so linking academic writing more clearly to events in the digital economy. Our volume also examines business models and change. It explores how the business model perspective increases our understanding of micro and macro change processes in particular, the critical question of how to achieve scale and scope, and the difference between social and other business models, how business models vary over the industry cycle and how different levels of management contribute to business model innovation.
Keywords: Business planning.; Strategic planning.; Business & Economics -- Strategic Planning.; Business strategy.; elektronické knihy; electronic books